H. 1048-1049/M. 1638-1639 TARİHLİ HARPUT ŞER?İYYE SİCİLİ: TRANSKRİPSİYON VE DEĞERLENDİRME - UZUN, CELALETTİN (Fırat Üniveristesi, 2011)
Bu çalışma Harput Kazası'nın 1638-1639 tarihli Şer?iyye Sicilinin transkripsiyon ve değerlendirmesini içermektedir. Çalışmada, öncelikli olarak Osmanlı Devleti'nde kadılık kurumu, şer?iyye mahkemeleri ve şer?iyye sicilleri hakkında bilgi verildikten sonra, söz konusu sicil içindeki belgeler özetlenip, bunların konularına göre tasnifi ve genel değerlendirmesi yapılmıştır. Bundan sonra ise transkripsiyon metnine yer verilmiştir.İncelediğimiz Harput Şer`iyye Sicili ferman, berat, buyruldu, tezkere ve mektup gibi belgelerin suretleri ile alım-satım, borç tescilleri, miras davaları, vasi tayini, nafaka, mehir, yapılan sulh akideleri, vergi, emlak, yol anlaşmazlığı vb. belgeleri içermektedir. Bütün bu belgeler ve bilgiler ışığında, Harput Sancağı'nın söz konusu tarihlerdeki siyasi, iktisadi ve sosyal durumu hakkında bazı tespitlerde bulunulmaya da çalışılmıştır. Ayrıca sicilin hazırlandığı dönem, 1638-1639 Bağdad Seferi ve sonrasına rastladığı için, seferden dönen padişah ve askerlerin iaşe ihtiyaçlarının giderilmesi konusunda da önemli bazı bilgiler bulunmaktadır. Yine sefere katılmayan bazı tımarlı sipahilerin tımarlarının ellerinden alınarak daha liyakatli kişilere verilmesiyle ilgili emirler de yer almaktadır. Bütün bunlardan başka, Harput'ta meydana gelen eşkıyalık olayları ve devletin bu olaylara karşı almış olduğu tedbirler, halktan kanuna aykırı olarak vergi talep edilmesi, köylüler arasındaki çeşitli anlaşmazlıklar, yaralama ve darp olayları gibi, muhtelif konular da defterde yer almaktadır.

This study includes transcription and assessment shari?ah register of regin of Harput dated 1638-1639. As a primarily in the study and giving informations about institution of the qadiness in the Ottoman Empire, shari?ah courts, shari?ah records and after that are going to summarizing the documents of the register and then would make to classified and the general assessment as a result. According to give it a place in transcription of text.The record book which has been reviewed by us, it includes in order to firmans which as they have been sent to Harput and letters patent, orders who wrote in one letter, missive, purchase and sale and their copies, which resemble such as documents of letters, the registrations of debt, inherited cases, appointment of guardian, alimony, dowry for bride, the peace convictions, tax, real estate property, road disputes and etc. All these documents and in way of the light of the informations which try to make determinations about the economic and social status of the banner of Harput with related dates.The period of the register is related betwen 1638 and 1639 what would make it so importent in the dates. Briefly we can say that the information of the period is registered in the register as well, would giving us that information about the expedition of bagdag which sultan and his soldeirs had gotten overcome to risk of needs of board themselves until returning from the expedition. Also it includes some information about the orders which had been given about cavalries who had not gone to the expedition therefore they had been taken back their feoffment for giving on other grup of cavalry who were deserved this application more than them. The record book includes these all as well; The acts of banditry are occurred in Harput and government of state how reacted on this events, the tax demanded from public under an unfair amount in contravention of the law, specific disputes between of villagers and wounding and assault incidents.
H. 1048-1049/M. dated 1638-1639 Harput Shari?ah Registery: Transcription and evaluation
Keywords: Tarih; Hukuk